Radiolysis of Potassium Picrate in 77 K; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Yakubik D. G.; Pak V. Kh.; Ananev V. A.; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (2016, 2016)
Title screen